PENGARUH PEMANFAATAN DIGITAL MARKETING TERHADAP KEBERLANGSUNGAN KEGIATAN UMKM DI DESA CEMPEDAK LOBANG KECAMATAN SEI RAMPAH KABUPATEN SERDANG BEDAGAI - Novita, Cici; Malik, Abdul (JURNAL MUTIARA MANAJEMEN, 2021)
This study aims to analyze the influence of digital marketing on the sustainability of MSME activities in Cempedak Lobang Village, Sei Rampah District, Serdang Bedagai Regency. In this study, the authors used quantitative data analysis with a population of 475 people who were SMEs in Cempedak Lobang Village, Sei Rampah District, Serdang Bedagai Regency. The sample in this study was obtained using the Slovin formula with an error rate of 10% so that the sample of this study was obtained as many as 83 MSME actors. To find out the results of the study, the authors used research instrument tests, simple linear regression test, t test (partial) and the coefficient of determination test using the SPSS version 20.0 application for windows. The results of a simple linear regression test obtained the equation Y = 24,173 + 0.455X, a positive regression coefficient value indicates that digital marketing has a positive effect on the sustainability of MSME activities. The value of tcount = 4.704 > ttable 1.66388 and a significance of 0.000 <0.05, which means that the digital marketing variable has a positive influence on the sustainability of MSME activities in Cempedak Lobang Village, Sei Rampah District, Serdang Bedagai Regency. The coefficient of determination (R2) of the regression results is 0.215 or 21.5%, meaning that the digital marketing variable explains its contribution to the sustainability of MSME activities by 21.5% while the remaining 78.5% is influenced by other variables not examined in this study.